2014
DOI: 10.12692/ijb/5.9.99-106
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of lactic acid bacteria against Fusarium oxysporum f. sp. albedinis isolated from diseased date palm in south Algeria

Abstract: In this study, four lactic acid bacteria (Lactococcus lactis subsp. lactis, Lactococcus lactis subsp. lactis biovar. diacetylactis, Leuconostoc mesenteroides subsp. mesenteroides and Leuconostoc mesenteroides subsp. mesenteroides biovar. dextranicum) were screened in vitro for antifungal activity against twelve strains of Fusarium oxysporum f. sp. albedinis (Foa), causal agent of the "Bayoud", the most destructive disease of date palm (Phoenix dactylifera L.) in Algeria. The results of the direct confrontation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 10 publications
0
0
0
Order By: Relevance
“…Significant growth inhibition was, however, obtained in another study for F. oxysporum [43]. Antifungal activity was previously indicated for Leuconostoc mesenteroides against R. solani [42] and F. oxysporum [43]. Our study confirmed these results only for a single strain of L. mesenteroides (out of nine tested).…”
Section: Antimicrobial Activity Of Lactic Acid Bacteria In Vitrosupporting
confidence: 80%
See 1 more Smart Citation
“…Significant growth inhibition was, however, obtained in another study for F. oxysporum [43]. Antifungal activity was previously indicated for Leuconostoc mesenteroides against R. solani [42] and F. oxysporum [43]. Our study confirmed these results only for a single strain of L. mesenteroides (out of nine tested).…”
Section: Antimicrobial Activity Of Lactic Acid Bacteria In Vitrosupporting
confidence: 80%
“…Khalaf and Raizada [42] also reported no activity of L. lactis against R. solani. Significant growth inhibition was, however, obtained in another study for F. oxysporum [43]. Antifungal activity was previously indicated for Leuconostoc mesenteroides against R. solani [42] and F. oxysporum [43].…”
Section: Antimicrobial Activity Of Lactic Acid Bacteria In Vitromentioning
confidence: 84%